Bleb grading by photographs versus bleb grading by slit‐lamp examination. Issue 5 (30th December 2019) - Hoffmann, Esther M.; Herzog, Daniel; Wasielica‐Poslednik, Joanna; Butsch, Christina; Schuster, Alexander K.
Abstract: Purpose: Using a bleb‐grading system clinically facilitates long‐term follow‐up of patients with previous glaucoma surgery. Clinical evaluation of these patients can be challenging for untrained ophthalmologists. Morphological bleb configuration might influence planning of follow‐up visits in glaucoma patients due to different and individual prognosis after trabeculectomy. In this study, we compared the MaBAGS (Mainz Bleb Appearance Grading System), a classification system for filtering blebs with other classification systems (MBGS/Moorfields Bleb Grading System, IBAGS/Indiana Bleb Appearance Grading Scale) in reference to usability and reliability and compare it to grading by bleb photographs. Methods: Forty‐two eyes of 31 patients after trabeculectomy were included. Three observers, two senior and one junior observer, graded all blebs using MaBAGS, MBGS and IBAGS during slit‐lamp examination. Bleb photographs were reviewed at least 4 weeks after clinical examination. Statistical analysis was performed to determine agreement between the observers using intraclass correlation coefficients. Results: With MaBAGS, excellent and good levels of agreement were found for vascularity indices, Seidel test and transparency. Parameters for area and height yielded moderate agreement, while indices for conjunctival mobility and microcysts failed to show satisfying levels of agreement. Using MBGS resulted in excellent and good interobserver consistency for parameters regarding subconjunctival blood, Seidel test, and central and peripheral vascularity. Height and nonbleb vascularity reached moderate levels of agreement. Agreement for area parameters was low. With IBAGS, good levels of agreement were found for height and vascularity, and moderate for extent. In all grading systems, consistency was considerably better between the two experienced observers compared to the inexperienced grader. Conclusions: MaBAGS shows good reproducibility. Using such a grading system improves precision of the description of a highly variable clinical finding. The reliability of grading by slit‐lamp examination exceeds that of grading on photographs.